Alcohol use pattern among homeless adult men in Belo Horizonte - Botti, Nadja Cristiane Lappann; Castro, Carolina Guimarães de; Silva, Ana Karla; Silva, Monica Ferreira da; Oliveira, Ludmila Cristina de; Castro, Ana Carolina Henriques Oliveira Amaral de; Fonseca, Leonardo Leão Kahey (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2010)
This descriptive, epidemiologic study aimed at identifying the prevalence of alcohol use among the homeless population. Data collection was performed using AUDIT with 245 men living on the streets of Belo Horizonte. It was found there is a high frequency of harmful alcohol use pattern with probable dependence in mature adults and a high rate of risk pattern for those living on the streets for over 6 years and among those sleeping in public areas. This study highlights the importance of building health policies that are aimed at the homeless population.